Extraperitoneal bladder rupture with severe lacerations of the urogenital diaphragm: a case report - Hagiwara, Akiyoshi (BioMed Central, 2009)
BACKGROUND: A 65-year woman injured by automobile had an open-book type pelvic fracture and extraperitoneal bladder rupture. CASE PRESENTATION: Non-surgical management was selected because of suspected minor leakage. A follow-up CT cystography on day 21 showed a large urinoma. In the sagittal reconstruction CT images, the bladder was displaced downwards. Surgery was performed. Surgical findings showed that the bladder neck and the urethra were not anchored because of a laceration in the urogenital diaphragm. The bladder base had descended to the inferior margin of the pubic bone and a laceration of about 3 cm was found in the anterior surface of the bladder neck. The laceration was sutured, and the wall of the urinoma was extensively resected. The postoperative course was uneventful. CONCLUSION: An extraperitoneal bladder rupture associated with a severe laceration in the urogenital diaphragm will be indicated for surgery when the bladder is not anchored and healing is prevented. Sagittal reconstruction CT cystography was effective for this diagnosis.